Antipsychotic Drug Prescription in Pediatric Intensive Care Units: A 10-Year U.S. Retrospective Database Study - Madden, Kate; Wolf, Michael; Tasker, Robert C.; Figueroa, Janet; McCracken, Courtney; Hall, Matt; Kamat, Pradip (Journal of Pediatric Intensive Care, 2021)
Delirium recognition during pediatric critical illness may result in the prescription of antipsychotic medication. These medications have unclear efficacy and safety. We sought to describe antipsychotic medication use in pediatric intensive care units (PICUs) contributing to a U.S. national database. This study is an analysis of the Pediatric Health Information System Database between 2008 and 2018, including children admitted to a PICU aged 0 to 18 years, without prior psychiatric diagnoses. Antipsychotics were given in 16,465 (2.3%) of 706,635 PICU admissions at 30 hospitals. Risperidone (39.6%), quetiapine (22.1%), and haloperidol (20.8%) were the most commonly used medications. Median duration of prescription was 4 days (interquartile range: 2–11 days) for atypical antipsychotics, and haloperidol was used a median of 1 day (1–3 days). Trend analysis showed quetiapine use increased over the study period, whereas use of haloperidol and chlorpromazine (typical antipsychotics) decreased (p < 0.001). Compared with no antipsychotic administration, use of antipsychotics was associated with comorbidities (81 vs. 65%), mechanical ventilation (57 vs. 36%), longer PICU stay (6 vs. 3 days), and higher mortality (5.7 vs. 2.8%) in univariate analyses. In the multivariable model including demographic and clinical factors, antipsychotic prescription was associated with mortality (odds ratio [OR] = 1.09, 95% confidence interval [CI]: 1.02–1.18). Use of atypical antipsychotics increased over the 10-year period, possibly reflecting increased comfort with their use in pediatric patients. Antipsychotics were more common in patients with comorbidities, mechanical ventilation, and longer PICU stay, and associated with higher mortality in an adjusted model which warrants further study.
Keywords: antipsychotic; delirium; pediatric critical care